Sam Sharpe: The Scriptures that Motivated Him and their Implications for Today - Fiddes, Paul S. (Baptist quarterly, 2024)
Sam Sharpe, an enslaved person and initiator of the rebellion of enslaved peoples in Jamaica, 1831–2, was a Baptist deacon who knew the Bible well. While biographies and accounts of the rebellion cite a number of texts that the writers believe motivated Sam Sharpe in his actions, we only have undisputed evidence for his appeal to four specific texts (Matthew 5:33–37, Matthew 6:24 // Luke 16:13, 1 Corinthians 7:20–21, Philippians 2:12); our knowledge of his use of these is to be gleaned from the records of his trial, together with the reports of two missionaries who visited him in prison. This article shows that it is nevertheless possible from these accounts to deduce significant insights into his interpretation of scripture and its effect on his extraordinary leadership in the events of the time. Correspondingly, this hermeneutic can offer guidance for modern movements for peace, justice and freedom.